Ground State Cross-Coupling of Haloarenes with Arenes Initiated by Organic Electron Donors, Formed in situ: An Overview - Nocera, Giuseppe; Murphy, John A. (Synthesis, 2020)
Many reactions have been discovered that lead to coupling of haloarenes to arenes using potassium tert-butoxide as the base, and one of a variety of organic compounds as an additive. The organic additive reacts with the base to form a strong organic electron donor in situ that initiates a base-induced homolytic aromatic substitution (BHAS) coupling reaction, by converting the haloarene into an aryl radical. This brief report presents an overview of the wide range of organic additives that can be used, and the organic electron donors that they form.
Keywords: electron transfer; initiation; BHAS coupling; organic electron donor; radical reaction